Hubungan Sikap Ibu tentang Pijat Bayi dengan Perilaku Ibu dalam Memijat Bayi - Safitri Safitri (Universitas Baiturrahim, 2020)
ABSTRACTMassage is an art of medical care and treatment that has been practiced since years ago. Massage can be done at any age, including infants. Touch and massage to new born can guarantee continuous skin contact that can maintain the feeling of safety in infants. The public health center Putri Ayu is the public health center with the highest number of infants with 0-11 months in Jambi city which is 917 infants in 2019. Information obtained from one of the officers, that there is no training and infant massage class at public health center Putri Ayu. This study is a quantitative study, with a cross sectional design that aims to determine the relationship between maternal attitudes about infant massage and maternal behavior in massaging infants in the public health center Putri Ayu, Jambi city. Data collection on attitudes and behaviors using a questionnaire. As many as 43 study subjects were selected by accidental sampling. This study was analyzed using the chi square statistical test. The results of the study there is a relationship between maternal attitudes about infant massage with maternal behavior in massaging babies (p-value = 0.044 <alpha 0.05). From the results of this study it is expected that the public health center will participate in training and open baby massage class so that mothers who have babies are interested in doing baby massage.